KOMUNIKASI INTERPERSONAL KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA - Muhtadin, Muhtadin (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2014)
The Influence of Leadership Interpersonal Communication of School Principal and Organizational Culture on Teachers Working Satisfaction of Al Islam Senior High School of Surakarta. The problem raised in this study is whether leadership interpersonal communication of school principal and organizational culture influence teachers working satisfaction. To be more specific, this study is intended to answer the following research questions: 1) The influence of leadership interpersonal communication of school principal on teachers working satisfaction. 2) The influence of organizational culture on teachers working satisfaction. 3) The influence of both leadership interpersonal communication of school principal and organizational culture influence teachers working satisfaction. This study is a quantitative research using causal correlational approach with theory of S-O-R. The population of this study is all teachers in the Senior High School of Al Islam Surakarta. The sampling used in the study is total sampling and therefore all teachers (N = 155) are sampled. The data are gathered through questionnaire. Using SPSS, both basic and multiple regression is used to analyze the data. The findings of the study show 1) The results of t-test a) There is a significant influence of interpersonal communication of school principal on teachers working satisfaction. The t-test shows that t 2,339 t table 1,975. b) There is a significant influence of organizational culture on teachers working satisfaction. The t-test shows that t 4,504 t table 1,975. 2) The results of F test a) The F test shows that both leadership interpersonal communication of school principal and organizational culture simultaneously influence teachers working satisfaction. This conclusion is based on the coefficient of F 27,863 which is higher than the coefficient of F table 3,06 on the degree of significance p = .000. Based on the above findings, this study offers the following suggestions 1)The chair of Al Islam Foundation should improve the leadership interpersonal communication though various strategies such as leadership training. This is because this study finds that the variable of communication of the school principal directly influences the teachers working satisfaction around 2,339. 2) The school principal should improve the organizational culture in order to create a better working environment. 3)Future research should conduct similar research with qualitative approach in order to deeply understand factors related to the variables used in this study.